2014
DOI: 10.1097/opx.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Unique Hard Scleral Lens Post-LASIK Ectasia Fitting

Abstract: Severe neuronal loss in the hippocampus, that is, hippocampal sclerosis (HS), can be seen in 3 main clinical contexts: dementia (particularly frontotemporal lobar degeneration [FTLD]), temporal lobe epilepsy (TLE), and hippocampal ischemic injury (H–I). It has been suggested that shared pathogenetic mechanisms may underlie selective vulnerability of the hippocampal subfields such as the CA1 in these conditions. We determined the extent of neuronal loss in cases of HS-FTLD (n = 14), HS-TLE (n = 35), and H–I (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…None of the cases with CA1 lesions bordering CA2 presented with TDP‐43 or neurites. Our findings are in line with the location of hypoxic lesions reported in animal studies 40, 48, as well as results reported by Hatanpaa et al 23, who observed epilepsy‐associated and ischemic injury to be common in the proximal and middle CA1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…None of the cases with CA1 lesions bordering CA2 presented with TDP‐43 or neurites. Our findings are in line with the location of hypoxic lesions reported in animal studies 40, 48, as well as results reported by Hatanpaa et al 23, who observed epilepsy‐associated and ischemic injury to be common in the proximal and middle CA1.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the morphology and its strong association with hippocampal TDP‐43 pathology, this focal neuron loss in the end of CA1 is hypothesized to be of primary neurodegenerative origin. In line with these results, Hatanpaa et al 23 described severe neuron loss in FTLD to be consistently located in the distal CA1. Our findings on more extensive CA1 neuron loss reflect the pattern observed in focal lesions.…”
Section: Discussionsupporting
confidence: 61%
“…Whether full recovery is achieved or not, sustaining a TBI has been implicated as a risk factor for later development of neurodegenerative disorders, 3 including Alzheimer disease (AD) [3,4], with evidence demonstrating that risk increases with greater length of loss of consciousness [5,6] and severity [7]. In addition, repetitive mild TBIs have been controversially linked to chronic traumatic encephalopathy (CTE) [8,9], and while this link remains in question, recent evidence has shown that mild TBI may invoke a higher risk for dementia [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the actual existence of CTBI/CTE as distinct entity has been questioned (19), the essential neuropathological features of what had previously been called Dementia Pugilistica in ex-boxers (and is now usually referred to as CTE) had been described in the 1970s (20). Recently, an unprecedented interest in CTBI/CTE was triggered by case reports of CTE in well-known ex-NFL players (21, 22), as well as neuroimaging studies in aging NFL players (23).…”
Section: Discussionmentioning
confidence: 99%